Travertines of the Cantera San Antonio, municipality of Villa de Leyva - Colombia. Advances in physical and mineralogical characterization for use as an ornamental rock (Revista de Diavulgación L'esprit Ingénieux, 2020)
This article shows the results of the physical, mechanical and mineralogical characterization of the travertine, extracted in the San Antonio quarry, Villa de Leyva, used for more than fifty years, for architectural purposes, use in foundations, columns and other structural elements, among others.The material is evaluated through the application of NBR and UNE-EN standards for the characterization of ornamental rocks. The characteristics of mineralogical composition were evaluated by means of petrographic microscope observations and the properties of apparent density, apparent open porosity, apparent water absorption, permeability, capillary water absorption and compression resistance. The previous tests were made in order to determine, in a preliminary way, the characteristics that define its use as an ornamental rock and its correct implementation on site.The rock studied is a travertine, of sedimentary origin, composed of calcite (CaCO3), with smaller amounts of iron oxides, which appears in the form of micrite (calcareous mud) as a constituent of the matrix and in crystals of sparite defined as cementing or even as filling material for some fissures. The results of the tests indicate that travertine has a dry bulk density of 2.51 g / (cm ^ 3), saturated bulk density of 2.61 g / (cm ^ 3), porosity of 9.05%, absorption of 3.62% water, capillarity water absorption coefficient of24.14 g / m2 · s0.5 and compressive strength of 16 MPa.The material meets the usage specifications for internal wall cladding and internal and external facades. Copyright © L’Esprit Ingenieux
Keywords: Travertine; Calcite; Characterization; Petrography; Water properties; Capillary absorption; Compression